DEVELOPMENT OF LEADERSHIP QUALITIES OF STUDENT YOUTH STUDENT YOUTH - Khomenko-Semenova, Lesia; Selezen, Hanna; Lytvynchuk, Nataliia; Oksamytna, Lesia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article provides a theoretical analysis and an empirical study of the development of leadership qualities of student youth. The purpose of the article is the theoretical justification and empirical study of the manifestation of leadership qualities of student youth. The results. In the course of empirical research, it was possible to establish: according to the method "Diagnosis of leadership abilities" (E. Zharikov, E. Krushelnytskyi), we investigated that 35% (14 respondents from the sample) have leadership abilities expressed at a high level, 45% (18 respondents from the sample ) demonstrate an average level of manifestation of leadership abilities, 20% (8 respondents from the sample) showed a low level of leadership abilities. According to the "I am a leader" method, the results were obtained: 16 respondents (40%) had high indicators in the "ability to manage themselves" scale, high indicators were found in the "Availability of a creative approach" scale, 27 respondents - 67.5% of the sample. "Organizational abilities" and "Knowledge of the rules of organizational work" 60% (24 respondents from the sample) and 57.5% (23 respondents from the sample). The ratio of motives for achieving success and avoiding failure in % according to A. Rean's method showed that 32.5% (13 respondents from the sample) were motivated to achieve success; 35% (14 respondents from the sample) have motivation with a tendency to develop motivation to achieve success; 17.5% (7 respondents from the sample) have an undefined motivational pole; students who have a tendency to avoid failure make up 10% (4 respondents from the sample); 5% (2 respondents from the sample) are solely motivated to avoid failure. According to the method "Personality Self-Assessment Test: Ireal, I-Ideal" S.A. Budassi obtained the results: 12.5% (5 respondents from the sample) have high self-esteem, 77.5% (31 respondents from the sample) have average self-esteem, 10% (4 respondents from the sample) have low self-esteem. According to N. Hall's EQ test, on the scales of empathy and managing the emotions of other people, the average level clearly prevails - 57.5% and 55% each. High indicators are also observed in these scales - 32.5% and 22.5%, the lowest indicators are observed in the scales of self-motivation 50% and management of one's emotions 42.5%. Conclusion. In the course of the theoretical analysis, we determined the leadership qualities of student youth as a set of their stable personal properties that develop, manifest, develop in the process of joint educational and extracurricular activities, contribute to the achievement of their goals through activity, motivation, self-development, empathy, influence the behavior of others, be an example for them, to lead. Based on the analysis of literary sources and the definition of leadership qualities, we identified the structure of leadership qualities of student youth: organizational and communicative component (propensity for leadership, level of self-regulation, organizational skills); motivational and value component (motivation, striving for self-actualization, self-perception, self-evaluation); emotional-regulatory component (emotional intelligence, communication skills, empathy, openness). According to the results of the author's questionnaire, it was proved that students have a clear idea of what leadership is, what leadership qualities are inherent in a leader, what contributes to and hinders the development of leadership qualities of student youth, and revealed the average indicators of the presence of leadership qualities of student youth. We see further research in the development of a model for the development of leadership qualities of student youth.